Analysis of Safety from a Human Clinical Trial with Pterostilbene - Daniel M. Riche; Corey L. McEwen; Krista D. Riche; Justin J. Sherman; Marion R. Wofford; David Deschamp; Michael Griswold (Journal of Toxicology)
Objectives. The purpose of this trial was to evaluate the safety of long-term pterostilbene administration in humans. Methodology. The trial was a prospective, randomized, double-blind placebo-controlled intervention trial enrolling patients with hypercholesterolemia (defined as a baseline total cholesterol ≥200 mg/dL and/or baseline low-density lipoprotein cholesterol ≥100 mg/dL). Eighty subjects were divided equally into one of four groups: (1) pterostilbene 125 mg twice daily, (2) pterostilbene 50 mg twice daily, (3) pterostilbene 50 mg + grape extract (GE) 100 mg twice daily, and (4) matching placebo twice daily for 6–8 weeks. Safety markers included biochemical and subjective measures. Linear mixed models were used to estimate primary safety measure treatment effects. Results. The majority of patients completed the trial (91.3%). The average age was 54 years. The majority of patients were females (71%) and Caucasians (70%). There were no adverse drug reactions (ADRs) on hepatic, renal, or glucose markers based on biochemical analysis. There were no statistically significant self-reported or major ADRs. Conclusion. Pterostilbene is generally safe for use in humans up to 250 mg/day.